KEPEMIMPINAN KEPALA BIRO KESEJAHTERAAN SOSIAL SEKRETARIAT DAERAH PROVINSI KALIMANTAN BARAT - E.21108086, Widaningsih (FISIP Universitas Tanjungpura, 2013)
This thesis is intended to identify and examine the function of leadership in the implementation duties and functions: (1) as a determinant of direction (2) as a representative and spokesperson for the organization (3) as an effective communicator (4) as a mediator and (5) as an integrator. This study uses descriptive qualitative research conducted by two research steps, namely: conduct library research (library research) and field research (field research). Research sites in the Bureau of Social Welfare Secretariat of West Kalimantan Province, the subject of his research is the Bureau Chief, Chief, Chief Sub. Section, and employee / senior staff in every part of the Secretariat of Social Welfare Bureau of West Kalimantan Province.Keywords: Leadership Functions, Communicators, Mediator, Integrator, Bureau, Social Welfare, Sekretariata Regional, Provincial Government.